2020
DOI: 10.1186/s12879-020-4783-8
|View full text |Cite
|
Sign up to set email alerts
|

Plasma levels of interleukin 27 in falciparum malaria is increased independently of co-infection with HIV: potential immune-regulatory role during malaria

Abstract: Background: The immune response during falciparum malaria mediates both harmful and protective effects on the host; however the participating molecules have not been fully defined. Interleukin (IL)-27 is a pleiotropic cytokine exerting both inflammatory and anti-inflammatory effects, but data on IL-27 in malaria patients are scarce. Methods: Clinical data and blood samples were collected from adults in Mozambique with P. falciparum infection, with (n = 70) and without (n = 61) HIV-1 co-infection, from HIV-infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 42 publications
3
10
0
Order By: Relevance
“… Red, green, and yellow indicate increased, comparable, and decreased cytokine levels between the two groups, respectively. References in the figure [ 33 57 , 59 61 , 63 65 , 83 ]. …”
Section: Resultsmentioning
confidence: 99%
“… Red, green, and yellow indicate increased, comparable, and decreased cytokine levels between the two groups, respectively. References in the figure [ 33 57 , 59 61 , 63 65 , 83 ]. …”
Section: Resultsmentioning
confidence: 99%
“…Possibly adding support to the notion that IL‐27 is driving the CD4 hi CD38 hi phenotype in our patients with acute malaria is a recent paper by Oterdal et al . who found that IL‐27 levels are elevated in the plasma of adults living in malaria‐endemic areas with acute falciparum malaria 44 .…”
Section: Discussionmentioning
confidence: 98%
“…Human studies of IL‐27 in malaria are relatively scarce. In a cross‐sectional malaria study in Mozambique, higher plasma levels of IL‐27 in malaria patients correlated with levels of parasitemia; however, there was no correlation with the disease severity 91 . In studies of infants in Togo, however, plasma levels of IL‐27 were lower in malaria cases when compared to infection‐free controls, and the levels remained unchanged after malaria treatment 92 .…”
Section: Cytokine Environmentmentioning
confidence: 96%